An Analysis on User Needs for the Design of Liaocheng Canal’s ICH Serious Game - Ran Xu; Dolah, Jasni (International Journal of Computational and Experimental Science and Engineering, 2025)
The Liaocheng section of the Grand Canal is rich in intangible cultural heritage (ICH), but many local young people do not know about them. The main reason for this problem is that the way of displaying and disseminating Canal ICH is too traditional, lacks a sense of the times and participatory, and cannot satisfy the needs and aesthetics of young people. With the development of digital technology, serious games bring new opportunities to spread and learn ICH. However, ICH serious games in the current Chinese market face the problems of lack of user engagement and low user satisfaction. It becomes especially important to analyze user needs before game design and development. The purpose of this study is to collect users' requirements for the design of Liaocheng Canal's ICH Serious Game in order to determine the design strategy of this game. The study adopted a quantitative approach, using online questionnaires to survey users' design preferences for the game in four aspects: learning, storytelling, gameplay, and user experience. The results of this study show the prioritization of users' needs for each layer and element of the game, providing targeted insights for future development, as well as clarifying core needs and providing new design ideas and references for other ICH serious game developers.